Academic Senate Minutes 2015-01-29 - Academic Senate:::::::::
Chair Report. Agenda amended and approved. Senate Action for 12/11/14 – Approved. Faculty Eligible for Emeritus status – Frederick Griffin, Carol Harvey, Terry Lease, Perry Marker, Laxmi Tewari, and Ervand Peterson – Approved. President Report. Provost Report. Associated Students Report. Community College BA degree programs feedback. Vice Chair Report. Vice President of Administration and Finance Report. Statewide Senators Report. Review of alternative process for Senate meetings. EPC Report. FSAC Report. SAC Report. CFA Report. Staff Report.